Enhanced degradation of sulfamethoxazole by a novel Fenton-like system with significantly reduced consumption of H2O2 activated by g-C3N4/MgO composite. (15th February 2021) - Li, Tianyu; Ge, Lifa; Peng, Xingxing; Wang, Wei; Zhang, Weixian
Highlights: The g-C3 N4 /MgOH2 O2 Fenton-like system can degrade contaminant (SMX) efficiently. The g-C3 N4 /MgOH2 O2 can produce cyclical H2 O2 after adding a thimbleful of H2 O2 . The mechanisms include nonradical pathway ( 1 O2 ) and radical pathway (∙OH). A novel nonradical oxidation system with wider application range was predominated by  1 O2 . Abstract: Advanced oxidation processes (AOP) based on nonradicals have attracted growing attentions because nonradical systems require much less oxidants and have low susceptibility to radical scavengers. Herein, a novel Fenton-like system that utilizes nonradicals was explored. It was derived from g-C3 N4 /MgO activated H2 O2, and can reduce the H2 O2 stoichiometry from 0.94%−0.18% to 0.03%. Sulfamethoxazole (SMX), a widely used sulfonamide, was used as the model pollutant to evaluate the efficacy of the system. It was observed for the first time that organic pollutants can be degraded with singlet oxygen ( 1 O2 ) through a nonradical pathway in the g-C3 N4 /MgOH2 O2 system. The reduced H2 O2 consumption was the net result of continuously-recycled H2 O2 from the reactions between H2 O2 and g-C3 N4 /MgO. Based on experimental results and theoretical calculations, the synthesis of g-C3 N4 and MgO forms a N-Mg bond with strong ability to absorb electrons and the electron transfer of H2 O2 to N-Mg bonding is accelerated, activation of H2 O2 to generate 1 O2 . Experimental data showed that organic pollutants can be degraded rapidly over a wide pH range. Findings of this study point to a cyclical but stable Fenton-like system with reduced H2 O2 requirement for cost-effective remediation and treatment of organic pollutants and toxic wastes. Graphical abstract: Image, graphical abstract